Inter-healthcare Professions Collaboration: Educational and Practical Aspects and New Developments - Susan Cornell (Frontiers Research Topics, 2016)
Settings, such as patient-centered medical homes, can serve as ideal places to promote interprofessional collaboration among healthcare providers (Fjortoft et al., 2016). Furthermore, work together by teams of interprofessional healthcare students (Van Winkle, 2015) and even practitioners (Stringer et al., 2013) can help to foster interdisciplinary collaboration. This result occurs, in part, by mitigating negative biases toward other healthcare professions (Stringer et al., 2013; Van Winkle 2016). Such changes undoubtedly require increased empathy for other professions and patients themselves (Tamayo et al., 2016). Nevertheless, there is still much work to be done to foster efforts to promote interprofessional collaboration (Wang and Zorek, 2016). This work should begin with undergraduate education and continue throughout the careers of all healthcare professionals.